The efficacy and safety of continuous intravenous tirofiban for acute ischemic stroke patients treated by endovascular therapy: a meta-analysis - Wang, Mengmeng; Li, Jing; Zhang, Lingyu; Li, Nana; Li, Xuemei; Wang, Pengfei (Frontiers in Neurology, 2024)
Introduction Tirofiban is a non-peptide selective glycoprotein IIb/IIIa receptor inhibitor with a short half-life. The research assesses the efficacy and safety of continuous intravenous tirofiban in patients with acute ischemic stroke (AIS) undergoing endovascular therapy (ET). Methods A systematic search of Pubmed, Embase, Web of Science, and Cochrane Library databases is conducted from inception until January 26, 2024. Eligible studies are included based on predefined selection criteria. Efficacy outcomes (favorable functional outcome and excellent functional outcome) and safety outcomes (symptomatic intracranial hemorrhage [sICH], any intracranial hemorrhage [ICH], and 90-day mortality) are calculated using odds ratios (OR) and 95% confidence intervals (CI). Results A total of 4,329 patients from 15 studies are included in the analysis. The results indicate a significant trend toward favorable functional outcomes in the tirofiban group (OR, 1.24; 95% CI, 1.09–1.42; p = 0.001). In terms of safety outcomes, tirofiban does not increase the risk of sICH (OR, 0.90; 95% CI, 0.71–1.13; p = 0.35) or any ICH (OR, 0.97; 95% CI, 0.70–1.34; p = 0.85), but it significantly decreases 90–day mortality (OR, 0.75; 95% CI, 0.64–0.88; p = 0.0006). A subgroup analysis suggests that continuous intravenous tirofiban demonstrates better efficacy (OR, 1.24; 95% CI, 1.09–1.42; p = 0.001) for patients with AIS undergoing rescue ET with even better results when used in combination with intra–arterial and intravenous administration (OR, 1.25; 95% CI, 1.07–1.451; p = 0.005). Conclusion Continuous intravenous tirofiban is effective and safe for patients with AIS undergoing rescue ET, particularly when combined with intra-arterial tirofiban. Systematic review registration PROSPERO, identifier CRD42023385695.